2018
DOI: 10.1021/acs.iecr.8b01407
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production through Thermal Decomposition of Hydrogen Sulfide: Modification of the Sulfur Recovery Unit To Produce Ultrapure Hydrogen

Abstract: The main goal of this research is modification of the Claus process to produce ultrapure hydrogen through hydrogen sulfide decomposition. The furnace and catalytic reactors in the Claus process are equipped with coil and hydrogen perm-selective membrane tubes. In the proposed structure, hydrogen is produced in the coil furnace and separated from gas stream in the membrane reactors. The conventional and proposed processes are modeled on the basis of the mass and energy balance equations at steady state conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Facing traditional fossil fuels responsible for climate change and global warming, dihydrogen H 2 constitutes a clean energy carrier and sustainable alternative for meeting future energy demands . Nowadays, H 2 can be used either as an energy vector owing to its high mass energy density (123 MJ kg –1 ) or as a chemical reagent for the Haber–Bosch process . As an energy vector, it can be consumed into a fuel cell to produce electricity for mobility or to store the excess energy produced by intermittent and renewable energy sources .…”
Section: Introductionmentioning
confidence: 99%
“…Facing traditional fossil fuels responsible for climate change and global warming, dihydrogen H 2 constitutes a clean energy carrier and sustainable alternative for meeting future energy demands . Nowadays, H 2 can be used either as an energy vector owing to its high mass energy density (123 MJ kg –1 ) or as a chemical reagent for the Haber–Bosch process . As an energy vector, it can be consumed into a fuel cell to produce electricity for mobility or to store the excess energy produced by intermittent and renewable energy sources .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent proposal, Ghahraloud et al suggested a process to produce ultrapure H 2 by modifying the Claus process for the decomposition of H 2 S. 40 To enhance performance in the modified Claus process, coils and hydrogen-selective permeable tubular membranes were placed in both the furnace and catalytic reactors as shown in Figure 4. To produce H 2 , a coil furnace is used and the H 2 gas is directed through membrane reactors to eliminate contaminants from the gas stream.…”
Section: General Routes Of H 2 S Conversion To H 2 and Other Compoundsmentioning
confidence: 99%
“…Nowadays, it is used as a chemical reagent to desulfurize oil or produce ammoniac by Haber–Bosch process. [ 2 ] It is also an emerging fuel for mobility, and it could become a solution to store the excess of energy produced by intermittent and renewable sources of electricity. [ 3 ] Hydrogen is currently predominantly produced by steam reforming of methane, which is a polluting process leading to the emission of greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%